A history of artistic innovations of Chinese seal engraving schools - Han, Tianheng (SCPG Publishing Corporation, 2019)
"This book includes over 400 seal impressions and abundant historical materials of seal studies. It makes a comprehensive and systematic exposition of the emergence and development of seal engraving schools since the Ming and Qing Dynasties and explores the driving force for the seal art development in the 500 years"--Publisher's website